Famas Enterprise / Farhana Ismail ... [et al.] - Ismail, Farhana; Ismail, Siti Noor Rashidah; Yahya, Nur Ain Zuriati; Abdul Aziz, Nur Halimaton; Md Haris, Nur Atiqah Maulad (2014)
SEAWEED POP CRUNCH is a trading company that generally known one of SME which the selling is more concern on seaweed and popiah. SEAWEED POP CRUNCH consists of 5 partnership business whose will contribute same amount of capital and will hold different task responsibilities to manage this business. The nature of this business is selected through our reference and observation in long term planning in the nature of business. We have been making a long research about the planning in establishing in this business. as we known that, this product can be enjoyed by all people at the all ages. Popiah seaweed giving more satisfaction to people especially when consume it at free time. Finally, our future prospect of this business is to be known in the international level as a one stop food product that provide all type of popiah flavours around the world and really believe that users will love to come and buy our popiah seaweed.